UJI FUNGISTATIK EKSTRAK DAUN SIRIH (Piper betle L.) TERHADAP Candida albicans - Nurul Rahmah; Aditya Rahman KN (Universitas Lambung Mangkurat, 2010)
Betel (Piper betle L.) leaves are usually used by Indonesian people to treat candidacies and sprue. Such infections are commonly caused by Candida albicans. This research aim is to test antifungal effect of betel leaves towards C. albicans and determine in which concentration that it can affect the yeast. The result shows that the betel extract significantly affecting C. albicans cell number in concentration of 20%, 40%, 60%, 80%, and 100%. The extracts also significantly affecting its dry weight of C. albicans in concentration of 80% and 100%.